Pengaruh Motivasi dan Locus of control Terhadap Minat Entrepreneur Pada Mahasiswa STIEM Cilacap - Zamroni, Zamroni (JURNAL EKONOMI, 2016)
This study aims to examine and analyze the effect of motivation and locus of control on the entrepreneurial interest of students of STIE Muhammadiyah Cilacap.The sample in this study were students of STIE Muhammadiyah Cilacap totaling 50 respondents using interval data. This type of research was survey research using questionnaires, tests, interviews. In writing this thesis, the author will use two data sources consisting of primary and secondary data sources. Data analysis techniques used in the study using validity, reliability, classical assumption test, multiple linear regression analysis, hypothesis testing and determination test. The results showed X1 has a significant effect on entrepreneurial interest, X2 has a significant effect on entrepreneurial interest, X3 has a significant effect on interest entrepreneurship. X1, X2, simultaneously have a significant effect on interest in entrepreneurship with a contribution of 35.9%, while the remaining 64.1% is influenced by other factors not examined. Keywords: Motivation, Locus Of Control, and Entrepreneurial Interest.